Simulation of gas dynamics in plasma reactor for carbon dioxide conversion - Platonov, P.P.; Dudin, S.V.; Lisovskiy, V.A. (Вопросы атомной науки и техники, 2021)
Numerical simulation of a bulk-type plasma reactor for carbon dioxide conversion with distributed gas injection and pumping has been performed in hydrodynamic approximation by solution of Navier-Stokes equation using the mathematical package COMSOL. It is shown that the geometry of gas injection and pumping, which determines the trajectories of the particles and their residence time in reactor, can significantly affect the energy efficiency of the conversion. Different particles on their way from inlet to pumping hole move along different trajectories and spend different times inside the reactor. If the residence time of the gas in the reactor is less than optimal, the gas conversion will be incomplete. If this time is more than optimal, then an excessive amount of energy will be applied to the already converted gas. It is shown that the reactor height affects significantly the energy efficiency of plasma conversion of carbon dioxide.